Towards a critical geography of disaster recovery politics: Perspectives on crisis and hope. Issue 1 (January 2017) - Cretney, Raven Marie
Abstract: As disasters increasingly affect a greater proportion of the population with growing strength and frequency it is becoming even more important to comprehend how recovery from these events is mediated and managed by society. Emerging from several decades of concerted work on the social determinants of disaster, vulnerability and risk, research is now being established that underlies the importance of the politics and power in shaping the processes and outcomes of disaster recovery. In particular, there is a need to situate the central role of neoliberal capitalism in shaping the values and practices of reconstruction and recovery, particularly through engagements with crisis politics. At the same time, disasters may open up space for contestation and resistance that allows for alternative and transformative forms of recovery politics. In this paper I draw on geographies of crisis and hope to frame a theoretical perspective that encapsulates both the capitalist dynamics of disaster recovery and the radical potential of post capitalist politics for facilitating transformative action at the community scale.